Treatment with intravenous gammaglobulin in pediatric patients with primary vasculitis - Camacho Meza Ignacio; Yamazaki Nakashimada Marco Antonio (Instituto Nacional de Pediatría, 2014)
Nowadays intravenous immunoglobulins have been used in differ- ent vasculitis with various results for each condition, being more recommended for its use in Kawasaki disease and ANCA-associated vasculitis. However, there is still no solid evidence to support its use in the entire group of these diseases. We present a review of the existing literature related to the use of intravenous immunoglobulin for the treatment of primary vasculitis in childhood.